Tantangan dan Strategi Penerapan Berpikir Kritis pada Pembelajaran Online: Kajian Pustaka - Bachtiar (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2022)
Technological and critical thinking skills are two essential aspects of learning. The rapid development of technology and the demands of competition in the era of globalization force educators to be truly effective in maximizing existing and current learning technologies. Implementing online learning is believed to be inadequate without the ability to think critically. Critical thinking is an ability that is essentially needed for students in the present context. This paper discusses the challenges and strategies for applying critical thinking for students in online learning using a literature study approach. The study found that online learning can be an excellent tool to help students improve their critical thinking skills. The study also found that, despite the various challenges faced, critical thinking skills must still be encouraged and implemented in online learning because critical thinking skills will help students analyze their thoughts which will be the basis for making a choice and help them conclude. Implications and suggestions for further research are presented.